Maintenance management on wet market in zone II, Selangor / Nur Sri Fathihah Mohd Ishak - Mohd Ishak, Nur Sri Fathihah (Faculty of Architecture, Planning and Surveying, 2013)
This report is basically describes the research about the maintenance management at wet market on Zone II, Selangor. As we know, market commonly known as a place to sell a fresh foods such as fruits, fish, vegetables, meats and others. Currently, many places in this world have its own risk. Market also faced its own risk if the maintenance management does not maintain the market properly. The problem that usually occurs is the cleanliness of the wet market. It is because the lack of maintenance department to do maintenance work systematically. The objective of these researches is to study the maintenance management of wet markets, to determine the problems in maintenance management of wet markets and to recommend and improving maintenance management of wet markets. On this report it consists of introduction, literature review, research methodology, result and discussion and conclusion and recommendation. At the beginning, the report were describe the introduction that covers the study background, problem statement, aims and objectives, scope and limitation, research methodology and significant of study. The main focus is aims and objective that has to plan carefully in order to achieve it at the result and finding. After that, the chapter deeply discuss on the literature review about the problem faced in maintenance management of wet market. Then, on research methodology it will explain more about the strategy in order to get information about the research. Case study is important to discuss clearly about the topic that have been chosen. The analysis and finding will be discussed and the results are show in graph to make it more understanding.